Three‐Component Synthesis of Benzofuran‐3(2H)‐ones with Tetrasubstituted Carbon Stereocenters via Rh(III)‐Catalyzed C−H/C−C Bond Activation and Cascade Annulation. Issue 15 (8th July 2022) - Jiang, Jinyuan; Liu, Jidan; Yang, Zhenke; Zheng, Liyao; Liu, Zhao‐Qing
Abstract: An one‐pot three‐component synthesis of benzofuran‐3(2 H )‐ones with tetrasubstituted carbon stereocenters from salicylaldehydes, cyclopropanols, and alkyl alcohols via Rh(III)‐catalyzed C−H/C−C bond activation and cascade annulation has been successfully developed. Abstract :